Analysis of helminth communities of black grouse and ptarmigan in the Western Alps : conservation and management implications - N. Formenti; R. Viganò; M.C. Cerutti; N. Ferrari; P. Lanfranchi (European Wildlife Disease Association (E.W.D.A.), 2011)
In the Alps grouse populations have been declining in a more or less pronounced way, for several decades, and are endangered or extinct in many areas. Nevertheless, sanitary data are still poor and those concerning macroparasites usually derive from limited data collection and do not deepen ecological aspects. The present research has been carried out in Lepontine Alps (VB) in order to evaluate level of spatial interaction between black grouse (Tetrao tetrix) and ptarmigan (Lagopus mutus) populations which are in sympatric conditions in some periods of the year considering parasites as indicators for the environmental suitability and host’s health in order to compare their parasitological communities.Altogether the analyzed sample consists of 158 intestinal contents of black grouse and 42 of ptarmigan harvested between 2003 and 2007. Moreover 19 ptarmigan sampled in Canton Grigioni (CH) during the 2007 hunting season have been examined.Black grouse was infested by Ascaridia compar (p = 18,5% / 50%) and Aoncotheca caudinflata (p = 0,0% / 45%). As regards the 42 ptarmigan, only two adult females were infested by a single parasite identified as A. caudinflata. The Swiss sample shows A. compar (p = 11,7%, i = 4,0, a = 0,4) and C. caudinflata (p = 32,0%, i = 3,3 a = 1,1) as invasive species. Data collected on black grouse show a steady situation. Yet must be underlined the necessity of an in-depth study of the parasites’ role in the population’s dynamics and the fact that only two species of helminths have been found. The extremely depauperate parasite community of ptarmigan is an unusual picture which could be expression of an alteration in the host - parasite - environment relationship. This hypothesis is supported by the results of Swiss sample, collected in an area with a good ptarmigan population dynamics, which show a richer parasite community. It has to be considered that ptarmigan may suffer more than black grouse anthropic impact, destruction of the habitat and climatic changes. In this way it is desirable ...